Gut microbiota diversity after autologous fecal microbiota transfer in acute myeloid leukemia patients - Florent Malard; Anne Vekhoff; Simona Lapusan; Francoise Isnard; Evelyne D’incan-Corda; Jérôme Rey; Colombe Saillard; Xavier Thomas; Sophie Ducastelle-Lepretre; Etienne Paubelle; Marie-Virginie Larcher; Clément Rocher; et al. (Nature Communications, 2021)
The combination of chemotherapy and broad-spectrum antibiotics induces gut microbiota (GM) dysbiosis in acute myeloid leukaemia (AML) leading to additional complications. Here, the authors report the efficacy in GM restoration and safety of autologous faecal microbiota transfer in treated AML patients in a phase II clinical trial.